A Novel Blue to Transparent Polymer for Electrochromic Supercapacitor Electrodes. Issue 2 (12th December 2017) - Yuksel, R.; Ekber, A.; Turan, J.; Alpugan, E.; Hacioglu, S. O.; Toppare, L.; Cirpan, A.; Gunbas, G.; Unalan, H. E.
Abstract: Electrochromic supercapacitors may alert the user on the remaining capacity of the devices. The color change indicating the remaining capacity can be simply and rapidly recognized by the human eye or by optical instruments. A rapid indication of charged state may extend device service life and prevent overcharging, which would otherwise result in electrode aging and decomposition. In this study, a blue to the transmissive electrochromic polymer, poly(4, 7‐bis(2, 3‐dihydrothieno[3, 4‐B][1, 4]dioxin‐5‐YI)‐2‐(2‐octyldodecyl)‐2H‐benzo[D][1, 2, 3]triazole) (P1C), was used in nanocomposite form with transparent silver nanowire (Ag NW) network current collectors for the fabrication of electrochromic supercapacitor electrodes. Highly conductive and transparent Ag NW networks have an important role in the realization of electrochromic supercapacitors using P1C. Fabricated Ag NW/P1C nanocomposite electrodes had a specific capacitance of 65.0 F g −1 at a current density of 0.1 A g −1 . Nanocomposite electrode showed excellent stability (capacity retention of>98 %) after 11000 cycles associated with a resistance decrease associated with charge transfer. Abstract :